1966
DOI: 10.2466/pr0.1966.18.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Learning of Abstract Responses by Process and Reactive Schizophrenic Patients

Abstract: Sumnzary.-20 male patients rated as process schizophrenics were compared with 20 reactive schizophrenics and 20 non-psychiatric patients on a learning task designed to elicit increasing numbers of abstract responses. Only the process group did not manifest significant learning under the conditions of the study. Reactive schizophrenics and normals learned to respond more abstractly and there was no significant difference in over-all learning between these two groups. Results support the meacingfulness of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1969
1969
1981
1981

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…When schizophrenic 5s are divided into process (or "poor premorbid") and reactive (or "good premorbid") groups, the findings appear to be somewhat more consistent. Both Bleke (1955) and True (1966) reported results that show that normals and reactive schizophrenics are relatively insensitive to social censure, but that both groups differ significantly from the process schizophrenic group that did more poorly with censure, in support of the Rodnick and Garmezy position.…”
mentioning
confidence: 95%
“…When schizophrenic 5s are divided into process (or "poor premorbid") and reactive (or "good premorbid") groups, the findings appear to be somewhat more consistent. Both Bleke (1955) and True (1966) reported results that show that normals and reactive schizophrenics are relatively insensitive to social censure, but that both groups differ significantly from the process schizophrenic group that did more poorly with censure, in support of the Rodnick and Garmezy position.…”
mentioning
confidence: 95%
“…acu\e rather than chronic type (Salzinger & Portnoy, 1964). In related research, True (1962) found that reactive schizophrenics conditioned more rapidly than those classified as process. It has further been demonstrated by a number of research studies that schizophrenics respond or learn more under the conditions of verbal censure than verbal reward.…”
Section: University Of South Carolinamentioning
confidence: 93%
“…A number of investigations using behavioral measures of response to external stimulation (e.g. , DeWolfe, 1962;True, 1966;Smith, 1961;Moriarity and Kates, 1962;and Berman, 1963) found the reactives to be more responsive.…”
Section: The Process-reactive Distinctionmentioning
confidence: 99%